Fire Management for Healthy Rangelands in Sub-Sahara Africa - Louhaichi, Mounir; Olesikilal, Birikaa; Hassan, Sawsan (International Center for Agricultural Research in the Dry Areas, 2023)
This comprehensive review explores the historical and cultural significance of fire management in Sub-Sahara Africa's rangelands, emphasizing its integral role in socio-cultural practices and livelihoods. While traditional fire use aligns with herders' knowledge for optimal pasture management, recent limitations arise from government policies, erratic rainfall, and population pressures. The ecological effects of fire on rangelands showcase its potential for ecological renewal, influencing species diversity, biomass, and soil properties. The paper delves into strategic planning associated with implementing prescribed burning programs, aligning with FAO guidelines. Emphasizing the importance of monitoring and adaptive management, the review concludes with insights for policymakers, land managers, and practitioners, advocating for interdisciplinary collaboration and community engagement for sustainable prescribed burning programs in the region.